(untitled) (Bangladesh Journal of Pharmacology, 2016)
In modern era scientists have been trying to validate many properties of Allium species, especially in terms of the identity of the active components, their mechanism of action and exploring the potential benefits as food supplements. Thus, the present study has been designed to characterize the isolated cardioprotective compound from Allium humile leaves. Chromatographic purification of the methanolic extract of A. humile leaves isolated ajoene (enol form) (AH-1)- a new potent cardioprotective principle, along with three known compounds allicin (AH-2) and alliin (AH-3) and a flavonoid quercetin (AH-4). The structures of all the isolates (AH-1, AH-2) were characterized by using modern spectroscopic analysis UV, IR, 1H and 13C NMR and mass spectrometry. Furthermore, the new isolated compound pharmacologically conformed for cardioprotective effect. The data of known compounds (AH-2, AH-4) were further compared with the reported data for these compounds.